Neuropathic pain in end-stage hip and knee osteoarthritis: differential associations with patient-reported pain at rest and pain on activity. Issue 3 (March 2018) - Power, J.D.; Perruccio, A.V.; Gandhi, R.; Veillette, C.; Davey, J.R.; Syed, K.; Mahomed, N.N.; Rampersaud, Y.R.
Summary: Objective: We investigated whether pain at rest and pain on activity were differentially associated with neuropathic pain scores in individuals with end-stage hip and knee OA. Design: Study participants were 843 patients with hip or knee OA scheduled for total joint arthroplasty. In pre-surgery questionnaires, measures of socio-demographics, health status, medication use, neuropathic pain (painDETECT), pain at rest and pain on activity (WOMAC pain items), depression (HADS) and pain catastrophizing (PCS) were collected. Multivariable linear regression models were estimated for men and women separately to examine the association between neuropathic pain scores (outcome) and study measures, entered in blocks. Results: Sample mean age was 65.1 years (SD: 9.6); 57.1% were women. Mean painDETECT scores were significantly higher ( P  ≤ֹ 0.001) for women (11.2 ± 6.6 out of 38) than men (9.3 ± 7.0), with 35.6% of women and 27.7% of men meeting cut-offs for possible or likely neuropathic pain. In the final regression model for women, the coefficients for both types of pain were statistically significant, although the coefficient for pain at rest was 1.6 times greater than that for pain on activity. For men, only pain at rest was significantly associated with neuropathic pain scores. Conclusions: Findings support that possible neuropathic pain is experienced by a notable proportion of patients with end-stage hip and knee OA and is more strongly associated with pain at rest than pain on activity, particularly in men. Clinical presentation of pain at rest may warrant more thorough evaluation for potential neuropathic pain and have implications for appropriate pain management.